2008
DOI: 10.1590/s0034-72992008000300020
|View full text |Cite
|
Sign up to set email alerts
|

Interpretação e utilidade da prova calórica

Abstract: Cal oric testing is an otoneurologic evaluation of the status of the vestibular-ocular reflex; it allows an evaluation of each labyrinth separately. The main aspects on the use and interpretation of caloric testing are reviewed. Method: A systematic review of papers published in the past one hundred years on caloric testing was undertaken. The inclusion criteria were: cross-sectional, longitudinal, original articles, reviews and meta-analyses. Reviews of patient charts, case reports and editorials were exclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 48 publications
(83 reference statements)
0
3
0
1
Order By: Relevance
“…The angular velocity values of the slow component were also analyzed. We considered values under 5 degrees/second to represent hypofunction and values above 50 degrees/second to represent hyperfunction 3 , 14 , 15 . A morphologic or qualitative analysis of the CT recording was performed.…”
Section: Methodsmentioning
confidence: 99%
“…The angular velocity values of the slow component were also analyzed. We considered values under 5 degrees/second to represent hypofunction and values above 50 degrees/second to represent hyperfunction 3 , 14 , 15 . A morphologic or qualitative analysis of the CT recording was performed.…”
Section: Methodsmentioning
confidence: 99%
“…The bithermal caloric test was performed in all subjects in Group B to verify bilateral vestibular involvement. According to a previous study ( 26 ), a MSPV of less than 11°/sec under warm water stimulation and less than 6°/sec under cool water stimulation indicates a hypoactive semicircular canal. Specifically for BVD, a MSPV of less than 20°/sec resulting from the bithermal caloric test is an indicator of decreased VOR function ( 3 ).…”
Section: Discussionmentioning
confidence: 88%
“…It was observed that the population of those who (24). However, it can be stated that the cold caloric test was efficient in the removal of the influence of NEOF since after their application has been possible to reach definitive conclusions in 79% of those who had some influence NEOF and underwent this stimulation, according to the literature that the findings prove ice provides the most reliable diagnostic (12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%